Socially Oriented Formation of Business Relations: Partner Selection in Russian Retailing - Максим Евгеньевич Маркин (Journal of Economic Sociology, 2010)
The paper is devoted to formation of social relations among firms. To explain how business relations emerge of the author examines selection criteria used by retailers and their suppliers for finding exchange partners in the contemporary Russian consumer markets. Based on the structural (network) perspective in economic sociology the paper demonstrates that business partner selection mechanism is a complex procedure which cannot be reduced to evaluation of profitability of transactions but has to take into account identity of exchange partners. Empirical data were collected from a standardized survey of 500 managers of retailers and their suppliers in five cities of Russia.